(3aVGFd GdNdaGA GdCQHYI hZjQge QhGjI GHi GdMSf Hf CMeO Hf GdMSf GdMOGO GdebQFs - (3GdCUagGfj, CHh fYje, CMeO Hf YHO Gddg Hf CMeO Hf ESMGb, J (B430(3g`s
(3BNQgG (B:s
(3YdjgG UhQ SeGYGJ YOI efbhdI ef GdCUd GdPj fbdJ Yfg, hSeGY BNQ UMjM YdjgG gj HNW(B: (3jhSa Hf Ndjd Hf YHO Gddg GdOeTbjs
(3eUOQ GbJfGA GdCUd (B:s
(3aGVd CMeOs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdeYGQa GdYGeIs